METHODS OF BEHAVIOR CORRECTION IN THE PEDAGOGICAL PROCESS - Abdurakhimov Shogosim Abdurakhmonovich (Western European Studies, 2024)
In this article, thoughts on methods of pedagogical stimulation and behavior correction, giving recommendations on giving confidence, cheering up and supporting the student based on a positive assessment of his behavior and activities raised
Keywords: Education; behavior; organization of activities; reprimand